Study of Cotton in India 1963 - Committee on Natural Resources Planning Commission (Committee on Natural Resources Planning Commission Government of India, 1963)
The Study of Cotton in India (1963) presents a comprehensive analysis of cotton cultivation, production, marketing, and policy frameworks in post-independence India. It examines the impact of partition on cotton resources, the role of Five-Year Plans in expanding acreage and output, and the persistent challenge of low yields, particularly in rainfed areas. The study highlights the importance of improved seed varieties, fertilizers, irrigation, and mechanization in enhancing productivity. It also analyzes cotton marketing and pricing structures, emphasizing the wide price spread caused by intermediaries and the potential of cooperative marketing to improve farmers’ incomes. Long-term demand and supply projections underline the need for scientific agricultural practices and strategic investments to meet rising consumption. Overall, the document serves as a policy-oriented guide for strengthening India’s cotton sector through coordinated research, legislative support, and institutional reforms.
Committee on Natural Resources Planning Commission, New Delhi in Collaboration with Indian Central Cotton Committee, Bombay
Committee on Natural Resources Planning Commission, New Delhi in Collaboration with Indian Central Cotton Committee, Bombay
Keywords: Cotton Cultivation; Indian Cotton Economy; Five-Year Plans; Agricultural Productivity; Improved Seed Varieties; Irrigation Development; Cotton Marketing; Price Structure; Cooperative Marketing; Legislative Framework; Demand and Supply Projections; Textile Industry